A single element of multiband switched beam antenna for 5G applications - Pichaya Chaipanya; Marisa Punchin; Nopparat Prasoptunya; Wongsakorn Phothong-ngam (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This work proposes a simple design of switched beam antenna on square split-ring resonator to operate in multiband frequencies. The antenna is designed to support fifth generation (5G) wireless applications. The proposed antenna provides two different of the main beams, 45˚/225˚±5˚ and 135˚/315˚±5˚, by shorted circuit at 4 different edges. The designed antenna can support nine frequency bands, 7.071, 9.006, 9.321, 9.906, 10.428, 10.718, 12.967, 13.057 and 14.469 GHz, which are the high-band of 5G spectrum when shorted circuit to the ground conductor. The antenna provides maximum gain of 6.41 dBi. The dimension of the antenna is 6×6 mm2 which the thickness of 1.73 mm. The proposed design is based on a simple beam switching antenna configuration, compact size and low-cost manufacturing.